Axiological portrait of information society - Oleksander Dzeban; Olena Aleksandrova; Nataliia Vinnikova (Cхід)
The urgency of the issue is determined by an extent social discussion about the advantages and disadvantages of information process itself and application to the diverse social spheres, its problems and threatens. The main range of the problems is connected with the constant transformation and social variability, consequently with a change of worldview’s field of a person. The advantages of information society are traditionally connected with the constant development, creativity, freedom and discoveries of new ways of personal realization and communication possibilities. According to a principle of post-non-classical methodology, the authors study a problem of the value transformations in conditions of information society and determine the crucial contexts of infosociogenesis: a context of networked coordination, ethical context and symbolic context (namely, virtualization and mythologizing of information space). The realities of modern society form various even diametrically opposed values that lead to complete devaluation of each value and deprive a worldview of its principle of consolidation are considered in the issue. The authors describe the mechanisms of pe rson’s networked coordination and demonstrate that their action (constructive and destructive) facilitates in the general process of experience enrichment which is gained via a multiplicity and simultaneity of virtual practices in different spheres (simuclarization) and often mistakenly presented as a real experience of a person. The ethical transformations of information society are considered to be closely connected with an issue of personal social stability which is not often aware of the freedom limits in information space. The symbolic context of infosociogenesis in the form of virtualization and mythologizing is characterized by the creation and social inquiry of cultural forms which are produced by virtual patterns of the reality (simulacrums).